Novel Benefits of Remote Ischemic Preconditioning Through VEGF-dependent Protection From Resection-induced Liver Failure in the Mouse. Issue 5 (November 2018) - Kambakamba, Patryk; Linecker, Michael; Schneider, Marcel; Kron, Philipp; Limani, Perparim; Tschuor, Christoph; Ungethüm, Udo; Humar, Bostjan; Clavien, Pierre-Alain
Abstract : Objective: To investigate the impact of remote ischemic preconditioning (RIPC) on liver regeneration after major hepatectomy. Summary Background Data: RIPC is a strategy applied at remote sites to mitigate ischemic injury. Unlike other preconditioning approaches, RIPC spares target organs as it acts via systemic VEGF elevations. In the liver, however, VEGF is an important driver of regeneration following resection. Therefore, RIPC may have pro-regenerative effects. Methods: RIPC was applied to C57BL/6 mice through intermittent clamping of the femoral vessels prior to standard 68%-hepatectomy or extended 86%-hepatectomy, with the latter causing liver failure and impaired survival. Liver regeneration was assessed through weight gain, proliferative markers (Ki67, pH3, mitoses), cell cycle-associated molecules, and survival. The role of the VEGF-ID1-WNT2 signaling axis was assessed through WIF1 (a WNT antagonist) and recombinant WNT2 injected prior to hepatectomy. Results: RIPC did not affect regeneration after 68%-hepatectomy, but improved liver weight gain and hepatocyte mitoses after 86%-hepatectomy. Importantly, RIPC raised survival from 40% to 80% after 86%-hepatectomy, indicating the promotion of functional recovery. Mechanistically, the RIPC-induced elevations in VEGF were accompanied by increases in the endothelial transcription factor Id1, its target WNT2, and its hepatocellular effector β-catenin. WIF1 injection prior to 86%-hepatectomy abrogated the RIPC benefits, while recombinant WNT2 had pro-regenerative effects akin to RIPC. Conclusion: RIPC improves the regenerative capacity of marginal liver remnants in a VEGF-dependent way. If confirmed in patients, RIPC may become the preconditioning strategy of choice in the setting of extended liver resections. Abstract : Supplemental Digital Content is available in the text